Clinical efficacy of adalimumab in Crohn's disease: a real practice observational study in Japan. Issue 1 (December 2016) - Takeshima, Fuminao; Yoshikawa, Daisuke; Higashi, Syuntaro; Morisaki, Tomohito; Oda, Hidetoshi; Ikeda, Maho; Machida, Haruhisa; Matsushima, Kayoko; Minami, Hitomi; Akazawa, Yuko; Yamaguchi, Naoyuki; Ohnita, Ken; et al.
Abstract Background There are few reports of the efficacy of adalimumab (ADA) for clinical remission and preventing postoperative recurrence in Crohn's disease (CD) in Asian real practice settings. We conducted a Japanese multicenter retrospective observational study. Methods We evaluated patients with CD who were treated with ADA at 11 medical institutions in Japan to investigate the clinical efficacy of remission up to 52 weeks and the associated factors to achieve remission with a CD Activity Index (CDAI) < 150. The effects of preventing postoperative recurrence were also evaluated. Results In 62 patients, the remission rates were 33.9, 74.2, 75.8, 77.4, and 66.1 % at 0, 4, 12, 26, and 52 weeks, respectively. Although 10 patients discontinued treatment due to primary nonresponse, secondary nonresponse, or adverse events, the ongoing treatment rate at 52 weeks was 83.9 %. Comparison of remission and non-remission on univariate analysis identified colonic type and baseline CDAI value as significant associated factors (P  < 0.05). In 16 patients who received ADA to prevent postoperative recurrence, the clinical remission maintenance rate was 93.8 % and the mucosal healing rate was 64.3 % during a mean postoperative follow-up period of 32.3 months. Conclusions ADA effectively induced remission and prevented postoperative recurrence in patients with CD in a real practice setting.